Choroid plexus aging: structural and vascular insights from the HCP-aging dataset - Zhe Sun; Chenyang Li; Jiangyang Zhang; Thomas Wisniewski; Yulin Ge (Fluids and Barriers of the CNS)
Abstract Background The choroid plexus (ChP), a highly vascularized structure within the ventricles, is essential for cerebrospinal fluid (CSF) production and metabolic waste clearance, crucial for neurofluid homeostasis and cognitive function. ChP enlargement is seen in normal aging and neurodegenerative diseases like Alzheimer’s disease (AD). Despite its key role of in the blood-CSF barrier (BCSFB), detailed studies on age-related changes in its perfusion and microstructure remain limited. Methods We analyzed data from 641 healthy individuals aged between 36 and 90, using the Human Connectome Project Aging (HCP-A) dataset. Volumetric, perfusion, and diffusion metrics of the ChP were derived from structural MRI, arterial spin labeling (ASL), and diffusion-weighted imaging (DWI), respectively. Partial correlations were used to explore age-related ChP changes, and independent t-tests to examine sex differences across age decades. One-way ANOVA was employed to compare perfusion characteristics among ChP, gray matter (GM), and white matter (WM). Relationships between volume, perfusion, and diffusion were investigated, adjusting for age and sex. Additionally, the distribution of cyst-like structures within the ChP and their diffusion/perfusion MRI characteristics were analyzed across different age groups. Results The ChP undergoes notable changes with age, including an increase in volume (r 2  = 0.2, P < 0.001), a decrease in blood flow (r 2  = 0.17, P < 0.001), and elevated mean diffusivity (MD) values (r 2  = 0.16, P < 0.001). Perfusion characteristics showed significant differences between the ChP, GM, and WM (P < 0.001). Both the ChP and GM exhibited age-related declines in CBF, with a more pronounced decline in the ChP. A negative correlation was observed between the age-related increase in ChP volume and the decrease in CBF, suggesting compensatory dystrophic hyperplasia in response to perfusion decline. Cyst-like structures in ChP, characterized by lower MD and reduced CBF, were found to be more prevalent in older individuals. Conclusions Our findings provide a detailed quantitative assessment of age-related changes in ChP perfusion and diffusion, which may affect CSF production and circulation, potentially leading to waste solute accumulation and cognitive impairment. Grant support This work was supported in part by the NIH U01AG052564, P30AG066512, P01AG060882, RF1 NS110041, R01 NS108491, U24 NS135568.